(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In this study the novel spray pyrolysis technique, known as rotational, pulsed and atomized spray deposition method was used to fabricate vertically aligned and well separated FTO One-dimensional nanostructures on glass substrate. It was confirmed that spraying at low angle to the substrate is mandatory for the crystal growth of vertically aligned nanorods. The preferential orientation of nanorods crystallites along the (101) direction and prepared nanorods thin film showed an excellent transparency of 84.8% and a low resistance of 26.7 Î©/sq.